2010
DOI: 10.3354/meps08569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of larger heterospecifics and structural refuge on the survival of a coral reef fish, Thalassoma hardwicke

Abstract: Structural refuge and competition can influence the survival of coral reef fishes; however, the effect of structural refuge on the outcome of competition remains unclear. In Moorea, French Polynesia, surveys were used to quantify habitat association for juvenile Thalassoma hardwicke and 7 sympatric labroid species. Having identified the 3 species most similar to focal T. hardwicke in habitat association, a field assay was used to determine if the presence of larger individuals of these species adversely affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…We suggest that these reduced suites of mechanical features -low maxillary KT, small gape and low bite force -in Thalassoma wrasses may have evolved as a result of competitive displacement. Thalassoma wrasses co-occur, often in great abundance, in many tropical regions including but not limited to the Indian Ocean, the Indo-Pacific and the Caribbean (Randall et al, 1997;Geange, 2010;Geange et al, 2013;Froese and Pauly, 2014). In fact, field surveys conducted in the Indo-Pacific and Caribbean found that reef crests were typically numerically dominated by members of this clade (Bellwood et al, 2002).…”
Section: Why Clean?mentioning
confidence: 99%
“…We suggest that these reduced suites of mechanical features -low maxillary KT, small gape and low bite force -in Thalassoma wrasses may have evolved as a result of competitive displacement. Thalassoma wrasses co-occur, often in great abundance, in many tropical regions including but not limited to the Indian Ocean, the Indo-Pacific and the Caribbean (Randall et al, 1997;Geange, 2010;Geange et al, 2013;Froese and Pauly, 2014). In fact, field surveys conducted in the Indo-Pacific and Caribbean found that reef crests were typically numerically dominated by members of this clade (Bellwood et al, 2002).…”
Section: Why Clean?mentioning
confidence: 99%
“…These species have distinct functional niches; the former over‐associates with Porites rus , Turbinaria ornata and coral rubble (Geange 2010), feeding primarily on algae (Chen 2002). Pseudocheilinus hexataenia over‐associates with the structurally complex hard corals Pocillopora verrucosa and Porites rus (Geange 2010), feeding on copepods, amphipods, gastropods, shrimps and polychaete worms (Harmelin‐Vivien 1979). Conversely, the local realized niches of P. hexataenia and T. hardwicke were most similar.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the local realized niches of P. hexataenia and T. hardwicke were most similar. Like, P. hexataenia , T. hardwicke feeds primarily on small invertebrates (Myers 1999) and over‐associates with Pocillopora verrucosa and Porites rus (Geange 2010).…”
Section: Discussionmentioning
confidence: 99%
“…obs.). At our study site, juveniles of all 3 species use similar habitats; all 3 species form strong associations with massive Porites corals and Pocillopora verrucosa (Geange 2010). All 3 species also have similar diets, feeding predominantly on planktonic and benthic crustaceans (Randall 2005).…”
Section: Study Systemmentioning
confidence: 94%
“…Munday et al 2001, Almany 2003, and such interactions may determine the success of newly arrived indi viduals, e.g. if superior competitors ex clude inferior competitors from mutually preferred habitats (Robertson & Gaines 1986, Munday et al 2001, Geange 2010) and increase their exposure to predators (Holbrook & Schmitt 2002). Ultimately, a pattern of negative spatial co-variation between superior and inferior competitors may ensue, with important demographic consequences for subsequent life-history stages.…”
Section: Introductionmentioning
confidence: 99%